ONTOLOGICAL MODELING OF ASSURANCE EVALUATION IN THE CONTEXT OF FUNCTIONALLINGUISTIC APPROACH - Potiy, A. V.; Komin, D. S. (Radio Electronics, Computer Science, Control, 2011)
The functional-linguistic approach to security assurance evaluation is proposed. The procedure and results of assurance evaluation ontological analysis are described. Ontological modeling application to security evaluation is justified.